2009
DOI: 10.21273/hortsci.44.3.619
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity of Chinese Sand Pear Landraces (Pyrus pyrifolia Nakai) Using Simple Sequence Repeat Markers

Abstract: The sand pear (Pyrus pyrifolia Nakai) is an important fruit crop in China. In this study, simple sequence repeats (SSRs) were used to estimate the level and pattern of genetic diversity among 233 sand pear landraces collected from 10 different geographic regions in China. The results demonstrated that the SSR technique is an effective tool for assessing genetic diversity and the geographic pattern of genetic variation among sand pear landraces of different origins. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The AMOVA carried out with all loci showed that most of the existing variability was within groups (97%) rather than among groups (Table S8 ), which is in agreement with many outbreeding species and similar studies in pear (Jiang et al, 2009 ; Miranda et al, 2010 ; Wolko et al, 2015 ; Wuyun et al, 2015 ). Nonetheless, differences among the 4 groups (CV, LV, RS, and UA) were found in terms of the effective number of alleles and levels of heterozygosity.…”
Section: Resultssupporting
confidence: 86%
“…The AMOVA carried out with all loci showed that most of the existing variability was within groups (97%) rather than among groups (Table S8 ), which is in agreement with many outbreeding species and similar studies in pear (Jiang et al, 2009 ; Miranda et al, 2010 ; Wolko et al, 2015 ; Wuyun et al, 2015 ). Nonetheless, differences among the 4 groups (CV, LV, RS, and UA) were found in terms of the effective number of alleles and levels of heterozygosity.…”
Section: Resultssupporting
confidence: 86%
“…The history of pear breeding before the early modern period in Japan is still unclear, but some local cultivars may have been domesticated from Chinese materials. Jiang et al [ 42 ] suggested that there were opportunities for ancient cultivar exchange between Japan and eastern China. Thus, the “yellow” genetic background might have been introduced by genetic exchange with Chinese cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three species, P. pyrifolia is presumed to have been introduced into Japan prehistorically and became the major species in Japan [5]. Previous reports suggested that there were opportunities for ancient cultivar exchange between Japan and eastern China [6,7], but the varieties currently cultivated in Japan and China are genetically different from each other, suggesting that they have different breeding histories. In Japan, local cultivar 'Nijisseiki' has been one of the leading cultivars, and 'Nijisseiki' and its relatives have been repeatedly used as parents in breeding programs, suggesting that recent cultivars are de cient in genetic diversity [7].…”
Section: Introductionmentioning
confidence: 99%